The lipid peroxidation product 4-hydroxynonenal contributes to oxidative stress-mediated deterioration of the ageing oocyte - Bettina P. Mihalas (Nature Portfolio, 2017)
Abstract An increase in intraovarian reactive oxygen species (ROS) has long been implicated in the decline in oocyte quality associated with maternal ageing. Oxidative stress (OS)-induced lipid peroxidation and the consequent generation of highly electrophilic aldehydes, such as 4-hydroxynonenal (4-HNE), represents a potential mechanism by which ROS can inflict damage in the ageing oocyte. In this study, we have established that aged oocytes are vulnerable to damage by 4-HNE resulting from increased cytosolic ROS production within the oocyte itself. Further, we demonstrated that the age-related induction of OS can be recapitulated by exposure of germinal vesicle (GV) oocytes to exogenous H2O2. Such treatments stimulated an increase in 4-HNE generation, which remained elevated during in vitro oocyte maturation to metaphase II. Additionally, exposure of GV oocytes to either H2O2 or 4-HNE resulted in decreased meiotic completion, increased spindle abnormalities, chromosome misalignments and aneuploidy. In seeking to account for these data, we revealed that proteins essential for oocyte health and meiotic development, namely α-, β-, and γ-tubulin are vulnerable to adduction via 4-HNE. Importantly, 4-HNE-tubulin adduction, as well as increased aneuploidy rates, were resolved by co-treatment with the antioxidant penicillamine, demonstrating a possible therapeutic mechanism to improve oocyte quality in older females.